20h-18h-(-4h)+-h+3h=16

Simple and best practice solution for 20h-18h-(-4h)+-h+3h=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20h-18h-(-4h)+-h+3h=16 equation:


Simplifying
20h + -18h + -1(-4h) + -1h + 3h = 16

Remove parenthesis around (-4h)
20h + -18h + -1 * -4h + -1h + 3h = 16

Multiply -1 * -4
20h + -18h + 4h + -1h + 3h = 16

Combine like terms: 20h + -18h = 2h
2h + 4h + -1h + 3h = 16

Combine like terms: 2h + 4h = 6h
6h + -1h + 3h = 16

Combine like terms: 6h + -1h = 5h
5h + 3h = 16

Combine like terms: 5h + 3h = 8h
8h = 16

Solving
8h = 16

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Divide each side by '8'.
h = 2

Simplifying
h = 2

See similar equations:

| 15b-14b=5 | | 1/7.8 | | 0=x^2+3x-162 | | z^3=125 | | 17=K+-12 | | 4-5(x-3)+2x=-3 | | 45x+y=10 | | 4(7-1)=2z-4 | | 360=b-10 | | 1600/x^2 | | 5n-4=4+3n | | -7x+20=-3x-8 | | 2(x-5)+3=3(x+2)+8 | | T/42=1.5/3 | | -15u+13u=14 | | x=45+2 | | graphy^2=12x | | -3c-12=-5tc | | 5x=30x^2 | | 7(1-p)=-2(1-3p) | | 41-4x=0 | | 7-3x-7x+6= | | 2x-4z=0 | | D/4-9=–3 | | 6u-u+4u-9u+4u=16 | | 1(-4-3n)-8+2(n-3)= | | 16=9z-2-9(2z-5) | | (x-3)(x)(x+7)=360 | | 9-6x=3(6x-2) | | Y-17=-18 | | 3n+1=11 | | 4x^2-32x+y^2+8y+64=0 |

Equations solver categories